2021
DOI: 10.1111/cen.14410
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of gonadotropin‐releasing hormone analog treatment in children with idiopathic central precocious puberty: A systematic review and meta‐analysis

Abstract: Objective To investigate the long‐term efficacy and safety of gonadotropin‐releasing hormone analog (GnRHa) treatment in children with idiopathic central precocious puberty (CPP). Method The protocol was registered with International Prospective Register of Systematic Reviews (CRD42018102792). PubMed, EMBASE and the Cochrane Library were searched for eligible comparative and single‐arm studies. Results We identified a total of 98 studies that included 5475 individuals. The overall risk of bias of the eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
(49 reference statements)
0
22
0
1
Order By: Relevance
“…Until now, gonadotrophin-releasing hormone analog (GnRHa) is the only effective treatment for CPP among the currently available, which maintains the stable level of GnRH to reduce the steroid hormones to the prepubertal level. Several synthetic peptide drugs, such as leuprolide, triptorelin, and goserelin, have been used clinically [ 6 , 7 ]. GnRHa continuously stimulates the anterior pituitary through GnRH receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, gonadotrophin-releasing hormone analog (GnRHa) is the only effective treatment for CPP among the currently available, which maintains the stable level of GnRH to reduce the steroid hormones to the prepubertal level. Several synthetic peptide drugs, such as leuprolide, triptorelin, and goserelin, have been used clinically [ 6 , 7 ]. GnRHa continuously stimulates the anterior pituitary through GnRH receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, various common side effects of GnRHa have been reported, such as injection site reactions, sterile abscess, pain, bruising, and nausea [ 10 ]. In addition, there are no clear evidence of the effect of GnRHa treatment on increasing the adult height of girls with CPP aged between 6 and 8 years [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term results demonstrated improvements of adult height in both boys and girls. A recent systematic review and meta-analysis (98 studies, 5475 individuals) concluded that GnRH analog treatment increase adult height and decrease the body mass index in girls with idiopathic CPP in comparison with no treatment [79]. The same authors stated that GnRH analog treatment did not evidently increase the risk of PCOS [79].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (98 studies, 5475 individuals) concluded that GnRH analog treatment increase adult height and decrease the body mass index in girls with idiopathic CPP in comparison with no treatment [79]. The same authors stated that GnRH analog treatment did not evidently increase the risk of PCOS [79]. Even better outcome in terms of adult height seems to present in males, but few data are available and poor evidence on the reproductive function in adulthood are available in male sex [50,73,76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation